2020
DOI: 10.3389/fpls.2019.01735
|View full text |Cite
|
Sign up to set email alerts
|

Plant Phylogeny and Growth Form as Drivers of the Altitudinal Variation in Woody Leaf Vein Traits

Abstract: Variation in leaf veins along environmental gradients reflects an important adaptive strategy of plants to the external habitats, because of their crucial roles in maintaining leaf water status and photosynthetic capacity. However, most studies concentrate on a few species and their vein variation across horizontal spatial scale, we know little about how vein traits shift along the vertical scale, e.g., elevational gradient along a mountain, and how such patterns are shaped by plant types and environmental fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…Numerous studies have indicated that phylogeny has a significant effect on the functional trait composition and that the relationships among traits are generally weakened after removing phylogeny (Cadotte et al, 2019;Wang et al, 2020;. This study also found that the traits of coexisting species in the community had a phylogenetic structure; however, only a few leaf traits (LA and LT) showed strongly phylogenetic signals.…”
Section: Phylogenetic Effects On Leaf Functional Traitssupporting
confidence: 59%
“…Numerous studies have indicated that phylogeny has a significant effect on the functional trait composition and that the relationships among traits are generally weakened after removing phylogeny (Cadotte et al, 2019;Wang et al, 2020;. This study also found that the traits of coexisting species in the community had a phylogenetic structure; however, only a few leaf traits (LA and LT) showed strongly phylogenetic signals.…”
Section: Phylogenetic Effects On Leaf Functional Traitssupporting
confidence: 59%
“…Numerous studies have indicated that phylogeny has a significant effect on the functional trait composition and that the relationships among traits are generally weakened after removing phylogeny (Cadotte et al, 2019 ; Liu, Chen, et al, 2021 ; Liu, Li, et al, 2021 ; Wang et al, 2020 ). This study also found that the traits of coexisting species in the community had a phylogenetic structure; however, only a few leaf traits (LA and LT) showed strongly phylogenetic signals.…”
Section: Discussionmentioning
confidence: 99%
“…Above the minimum cell size defined by the size of the genome, leaf cell sizes and packing densities can vary in response to abiotic conditions (Blonder et al ., 2017, Veselý et al ., 2020, Wang et al ., 2020, Zhao et al ., 2020). Using the four species that occurred in more than one site (Table 2), we calculated the effects of MAT, MAP, and soil water salinity on each anatomical trait (Fig.…”
Section: Discussionmentioning
confidence: 99%